Benchmarking environmental impacts of power groups used in a designed UAV: Hybrid hydrogen fuel cell system versus lithium-polymer battery drive system. (1st January 2023) - Çalışır, Duran; Ekici, Selcuk; Midilli, Adnan; Karakoc, T. Hikmet
Abstract: This study investigates the environmental impacts of using two different power groups in a fixed-wing Unmanned Aerial Vehicle (UAV). The first power group consists of a conventional electric motor, a lithium polymer battery and a propeller. The second power group is the hybrid power group formed by adding the Proton Exchange Membrane (PEM) fuel cell. The life cycle assessment (LCA) method is applied to the configurations to reveal environmental impact values (global warming, terrestrial ecotoxicity, photochemical oxidation, acidification, eutrophication and so on). Inventory and impact analysis calculations are performed using SimaPro 9.1 software. Ecoinvent 3.6 database is employed in this software. The environmental impact assessment is made according to CML-IA Baseline and ReCiPe method. In addition, the research involves hotspot analyses for both power group configurations. Consequently, the following is noticed as a result of a transition from lithium-polymer power group to hybrid hydrogen fuel cell system; (i) the global warming reduces by 6.95%, (ii) the terrestrial ecotoxicity reduces by 6.35%, (iii) the photochemical oxidation decreases by 1.23%, and (iv) the ozone layer depletion increases by 12.44%. These days when environmental problems stand out, the effects of UAVs hybridized with fuel cells, known as a clean energy source, related with environmental problems reflect the principal of this research. Highlights: Environmental effects of UAV using two different power groups. Data collection during the manufacture of the UAV. Life cycle assessment of the Proton Exchange Membrane. Inventory analysis of the Hybrid Hydrogen Fuel Cell UAV. Impact assessment of the Hybrid Hydrogen Fuel Cell UAV.